2022
DOI: 10.3390/buildings12040453
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing Devices and Reinforcing Techniques for Extruded Cement-Based Materials: A Review

Abstract: The three-dimensional (3D) printing technique for cement-based materials has been actively investigated and utilized in civil engineering. However, there is no systematic review of the fabricating devices. This paper reviews the software and hardware for extrusion-based 3D concrete printing. Firstly, a dedicated tool path generating software is urgently needed to meet the cementitious printing applications and to improve printing quality with toolpath optimizations. Secondly, the existing printing equipment wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 131 publications
0
7
0
Order By: Relevance
“…The review study by (Cao et al, 2022) found four major techniques for reinforcing 3D printed elements. They are mixing reinforcing materials inside the mix, inserting reinforcing techniques across the layers, placing reinforcing materials between the layers, and embedding reinforcing materials inside the filaments between the layers.…”
Section: Reinforcement Techniques For Strength Enhancementmentioning
confidence: 99%
“…The review study by (Cao et al, 2022) found four major techniques for reinforcing 3D printed elements. They are mixing reinforcing materials inside the mix, inserting reinforcing techniques across the layers, placing reinforcing materials between the layers, and embedding reinforcing materials inside the filaments between the layers.…”
Section: Reinforcement Techniques For Strength Enhancementmentioning
confidence: 99%
“…In contrast to the three-axis gantry printers [29,31,32] for concrete applications, the six axes of the robot arm allows directly for rotation around all three axes. Therefore, a tilting of the extruder for controlling the print angle is possible.…”
Section: Traversing Mechanismmentioning
confidence: 99%
“…On larger scales, this is not realizable. However, with robotic fabrication, 6-axis printing can produce multidirectionally printed objects without rotation of the printing bed [27,29]. The bio-based material, presented in [22], shows the potential to exhibit the necessary shape robustness to realize multi-axial prints without bed inclination and prevent deformation due to gravitational loading.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers achieved micro-level spatial resolution using a nozzle of diameter 0.8 mm. [146] As construction-scale printing is achieved using printing nozzles of large dimensions (ranging from 30 to 50 mm), [141,142,147,148] achieving micrometer-scale spatial resolution with these printers is currently impossible. For instance, even a rectangular nozzle of 10 mm in height, which is commonly used for large-scale printing, can only generate a resolution of 10 mm, falling short of micrometer-range accuracy.…”
Section: Printing Accuracy Of the 3dgp Techniquementioning
confidence: 99%